Recipient site preparation by cryoblebbing in melanocyte keratinocyte transplantation procedure over the fingers in vitiligo: A pilot study. Issue 6 (7th September 2020) - El Hawary, Marwa; Bassiouny, Dalia Ahmed; Esmat, Samia; Sobhi, Rehab; Saleh, Marwah Adly; AbdelHalim, Dalia; Hegazy, Rehab; Gawdat, Heba; Ragab, Nanis; Samir, Nesrin; Sany, Iman
Abstract: Surgical treatment of vitiligo lesions over the fingers has poor outcome. In this intra‐patient comparative study, 12 patients with stable non‐segmental vitiligo (NSV) affecting the middle three fingers of one hand were included. Three variations were used in treatment of finger vitiligo lesions: minipuch grafting, melanocytes keratinocyte transplantation procedure (MKTP) preceded by cryoblebbing or full CO2 laser resurfacing of the recipient site. Liquid nitrogen was used to create blebs in one finger 24 hours before therapy. On the following day, the second finger was treated by minipunch grafting and the third finger was resurfaced by CO2 laser. A suspension was prepared and 0.1 mL was injected into each cryobleb. It was also applied to the resurfaced skin. All patients underwent topical PUVA therapy and were followed‐up for 12 months. Ten cases with 52 lesions completed the follow‐up period. About 4/18 lesions treated by cryoblebbing followed by MKTP showed ≥75% repigmentation while only 1/17 lesions treated by laser resurfacing + MKTP and 1/17 lesions treated by minipunch grafting showed 30% and 10% repigmentation, respectively. No complications occurred in MKTP treated lesions. Cryoblebbing of the recipient site seems to improve the outcome of MKTP in lesions over the fingers in stable NSV.